2013
DOI: 10.1021/es401346d
|View full text |Cite
|
Sign up to set email alerts
|

Culmination of Low-Dose Pesticide Effects

Abstract: Pesticides applied in agriculture can affect the structure and function of nontarget populations at lower doses and for longer timespans than predicted by the current risk assessment frameworks. We identified a mechanism for this observation. The populations of an aquatic invertebrate (Culex pipiens) exposed over several generations to repeated pulses of low concentrations of the neonicotinoid insecticide (thiacloprid) continuously declined and did not recover in the presence of a less sensitive competing spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 23 publications
3
51
1
Order By: Relevance
“…Recently, there has been a rapid decline in biodiversity in many ecosystems and this fact has been associated to environmental stressors such as pesticides in high concentrations, suspensions, and organic pollution, which are a threat to worldwide biota (Liess et al, 2013). Our research group has demonstrated testicular toxicity in Wistar rats exposed to sub-lethal doses of ametryn (Dantas et al, 2015), highlighting oxidative stress induction and decrease of Leydig cell and sperm number, corroborating this association.…”
Section: Introductionsupporting
confidence: 75%
“…Recently, there has been a rapid decline in biodiversity in many ecosystems and this fact has been associated to environmental stressors such as pesticides in high concentrations, suspensions, and organic pollution, which are a threat to worldwide biota (Liess et al, 2013). Our research group has demonstrated testicular toxicity in Wistar rats exposed to sub-lethal doses of ametryn (Dantas et al, 2015), highlighting oxidative stress induction and decrease of Leydig cell and sperm number, corroborating this association.…”
Section: Introductionsupporting
confidence: 75%
“…These sub-lethal effects could impair organisms in numerous ways, such as decreasing their reproduction efforts or their competitive ability (e.g. Liess et al, 2013). These could eventually lead to changes in their abundances, and consequently, to changes in community structure.…”
Section: Discussionmentioning
confidence: 99%
“…When acute effects are modelled, the maximum concentration over time may be most relevant (Liess and von der Ohe, 2005). However, culmination of sequential pulses of pesticides may need to be considered in cases where several pulses of pesticides affect individuals, cohorts or successive generations within a population (Liess et al, 2013). When simulating chronic effects and recovery, the decrease of the exposure concentration resulting from dissipation (the exposure regime) is important as well.…”
Section: Other Exposure Considerationsmentioning
confidence: 99%